Meta-analysis of genome-wide association studies identifies common variants associated with blood pressure variation in east Asians - Kato, Norihiro; Takeuchi, Fumihiko; Tabara, Yasuharu; Kelly, Tanika N; Go, Min Jin; Sim, Xueling; Tay, Wan Ting; Chen, Chien-Hsiun; Zhang, Yi; Yamamoto, Ken; Katsuya, Tomohiro; Yokota, Mitsuhiro; et al. (Nature genetics, 2011)
Norihiro Kato and colleagues perform a meta-analysis of genome-wide association studies to identify common variants associated with blood pressure variation in east Asians. They identify five new genome-wide significant signals and replicate seven loci previously discovered in populations of European ancestry. We conducted a meta-analysis of genome-wide association studies of systolic (SBP) and diastolic (DBP) blood pressure in 19,608 subjects of east Asian ancestry from the AGEN-BP consortium followed up with de novo genotyping ( n = 10,518) and further replication ( n = 20,247) in east Asian samples. We identified genome-wide significant ( P < 5 × 10 −8 ) associations with SBP or DBP, which included variants at four new loci ( ST7L - CAPZA1 , FIGN-GRB14 , ENPEP and NPR3 ) and a newly discovered variant near TBX3 . Among the five newly discovered variants, we obtained significant replication in the independent samples for all of these loci except NPR3 . We also confirmed seven loci previously identified in populations of European descent. Moreover, at 12q24.13 near ALDH2 , we observed strong association signals ( P = 7.9 × 10 −31 and P = 1.3 × 10 −35 for SBP and DBP, respectively) with ethnic specificity. These findings provide new insights into blood pressure regulation and potential targets for intervention.